Wolbachia‐induced apoptosis associated with increased fecundity in Laodelphax striatellus (Hemiptera: Delphacidae). Issue 6 (12th September 2018) - Guo, Y.; Hoffmann, A. A.; Xu, X.‐Q.; Zhang, X.; Huang, H.‐J.; Ju, J.‐F.; Gong, J.‐T.; Hong, X.‐Y.
Abstract: Wolbachia influence the fitness of their invertebrate hosts. They have effects on reproductive incompatibility and egg production. Although the former are well characterized, the mechanistic basis of the latter is unclear. Here, we investigate whether apoptosis, which has been implicated in fecundity in model insects, influences the interaction between fecundity and Wolbachia in the planthopper Laodelphax striatellus . Wolbachia ‐infected females produced about 30% more eggs than uninfected females. We used the terminal deoxyribonucleotidyl transferase (TDT)‐mediated dUTP‐digoxigenin nick end labeling staining to visualize apoptosis. Microscopic observations indicated that the Wolbachia strain w Stri increased the number of ovarioles that contained apoptotic nurse cells in both young and aged adult females. The frequency of apoptosis was much higher in the infected females. The increased fecundity appeared to be a result of apoptosis of nurse cells, which provide nutrients to the growing oocytes. In addition, cell apoptosis inhibition by caspase messenger RNA interference in Wolbachia ‐infected L. striatellus markedly decreased egg numbers. Together, these data suggest that w Stri might enhance fecundity by increasing the number of apoptotic cells in the ovaries in a caspase‐dependent manner. Our findings establish a link between Wolbachia ‐induced apoptosis and egg production effects mediated by Wolbachia, although the way in which the endosymbiont influences caspase levels remains to be determined.